2021
DOI: 10.3390/genes12071057
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Extracellular Vesicles and Their miRNA Cargo in Patients with Fabry Nephropathy

Abstract: Current biomarkers of Fabry nephropathy lack sensitivity in detecting early kidney damage and do not predict progression of nephropathy. Urinary extracellular vesicles (uEVs) and their molecular cargo could reflect early changes in renal impairment as they are secreted by the cells lining the urinary tract. We aimed to conduct a proof-of-concept study to investigate whether analysis of uEV characteristics and expression of uEV-derived microRNAs (miRNAs) could be applicable in studies to predict the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Alterations in over 100 circulating miRNAs were identified in blood samples from FD patients in treatment with ERT compared with untreated patients (Xiao et al, 2019). Increased expression of miRNA miR-29a-3p and miR-200a-3p were detected in urinary extracellular vesicles isolated from patients with FD nephropathy (Levstek et al, 2021) which associates with the progression of kidney damage (Maier et al, 2021); miR-let-7a and let-7d were significantly increased in FD after therapy and have been suggested as potential markers for enzyme activity and inflammation in FD patients (Maier et al, 2021). These data point at miRNA profiling as a powerful diagnostic tool of FD progression and drug testing, as well as indicators of the development of specific FD phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in over 100 circulating miRNAs were identified in blood samples from FD patients in treatment with ERT compared with untreated patients (Xiao et al, 2019). Increased expression of miRNA miR-29a-3p and miR-200a-3p were detected in urinary extracellular vesicles isolated from patients with FD nephropathy (Levstek et al, 2021) which associates with the progression of kidney damage (Maier et al, 2021); miR-let-7a and let-7d were significantly increased in FD after therapy and have been suggested as potential markers for enzyme activity and inflammation in FD patients (Maier et al, 2021). These data point at miRNA profiling as a powerful diagnostic tool of FD progression and drug testing, as well as indicators of the development of specific FD phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard Lange and colleagues have shown that miRNA 21 levels are increased in uEVs in individuals with diabetes as well as a mouse model of glomerulonephritis [74]. Similarly, unique miRNA profiles in uEVs have been reported in individuals with membranous nephropathy [75], hypertension with albuminuria [76], diabetic kidney disease [77], [78], SLE [79], and Fabry nephropathy [80]. Recently, Luan et al reported changes in the profile of circular RNAs in uEVs from individuals with IgA nephropathy as compared to healthy subjects [81].…”
Section: Evs In Glomerular Diseasementioning
confidence: 95%
“…Similarly, unique miRNA profiles in uEVs have been reported in individuals with membranous nephropathy, 90 hypertension with albuminuria, 91 diabetic kidney disease, 92,93 SLE, 94 and Fabry nephropathy. 95 Recently, Luan et al 96 reported changes in the profile of circular RNAs in uEVs from individuals with IgA nephropathy compared with healthy subjects. Thus, both the protein and nucleic acid composition of EVs seems to be altered in glomerular disease.…”
Section: Evs In Glomerular Diseasementioning
confidence: 99%
“…In general, the use of EVs could increase the sensitivity of biochemical assays by increasing the concentration of test material. If successful, this could improve both maternal and fetal patient management [113] .…”
Section: The Potential Of Evs As Biomarkers For Lsds In Diagnostics A...mentioning
confidence: 99%